2016
DOI: 10.1186/s12955-016-0504-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in Chinese family caregivers for elderly people with chronic diseases

Abstract: BackgroundInadequate studies have been conducted in China to examine quality of life in family caregivers. Quality of life in family caregivers for elderly people with chronic diseases was evaluated, and the demographic and characteristic factors of both elderly people and their caregivers were explored.MethodsThe 36-Item Short Form Health Survey (SF-36) was used to assess health-related quality of life in 407 family caregivers caring for elderly people with chronic diseases in six communities on the Mainland … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
97
3
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(114 citation statements)
references
References 27 publications
7
97
3
7
Order By: Relevance
“…Surprisingly, most caregivers of dialysis patients in our study were their spouses rather than children. This is different to the profile of Chinese caregivers of older adults who were more likely to be children or children‐in‐law than a spouse . However, in these studies, the recipients of care were at least 10 years older than the dialysis cohort in our study.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Surprisingly, most caregivers of dialysis patients in our study were their spouses rather than children. This is different to the profile of Chinese caregivers of older adults who were more likely to be children or children‐in‐law than a spouse . However, in these studies, the recipients of care were at least 10 years older than the dialysis cohort in our study.…”
Section: Discussioncontrasting
confidence: 82%
“…Other predictors of poorer caregiver QOL among Chinese caregivers of the elderly include higher subjective caregiver burden, lower income, spousal caregivers and multiple chronic illnesses and higher dependency among the cared for elderly . Another Chinese study found caregiver age had the greatest impact on PCS and caregiver social lives had the greatest impact on MCS . Previous studies have shown a higher depression score with lower caregiver income, a direct relationship between dialysis patient and caregiver depression score, younger caregiver age associated with poorer physical QOL, and less social support predicted worse mental QOL …”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study showed that nursing workers had better self‐reported physical health status and worse MH status compared with general population reference values (Wang, ). However, relatively better physical well‐being may have been one of the reasons for taking this job (Xie et al, ). As noted, a difference of more than three points was clinically meaningful (Ware Jr. & Sherbourne, ); therefore, nursing workers in the present study were mentally vulnerable regarding their VT and MH scores.…”
Section: Discussionmentioning
confidence: 99%
“…Age was also associated with caregiver burden for all family members. Older people have less than optimal physical health and social functioning while younger caregivers engage in more social activates as a relaxation from the stressful caregiving role (Xie et al, 2016). Older caregivers may need more help and resources in order to perform caregiver role within the family.…”
Section: Discussionmentioning
confidence: 99%